Oxidative phosphorylation enhances the leukemogenic capacity and resistance to chemotherapy of B cell acute lymphoblastic leukemia - Chen, Chiqi (Sci Adv, 2021)
How metabolic status controls the fates of different types of leukemia cells remains elusive. Using a SoNar-transgenic mouse line, we demonstrated that B cell acute lymphoblastic leukemia (B-ALL) cells had a preference in using oxidative phosphorylation. B-ALL cells with a low SoNar ratio (SoNar-low) had enhanced mitochondrial respiration capacity, mainly resided in the vascular niche, and were enriched with more functional leukemia-initiating cells than that of SoNar-high cells in a murine B-ALL model. The SoNar-low cells were more resistant to cytosine arabinoside (Ara-C) treatment. cyclic adenosine 3′,5′-monophosphate response element–binding protein transactivated pyruvate dehydrogenase complex component X and cytidine deaminase to maintain the oxidative phosphorylation level and Ara-C–induced resistance. SoNar-low human primary B-ALL cells also had a preference for oxidative phosphorylation. Suppressing oxidative phosphorylation with several drugs sufficiently attenuated Ara-C–induced resistance. Our study provides a unique angle for understanding the potential connections between metabolism and B-ALL cell fates.